Molecular markers for quantification of bioactive fungal strains associated with Pinus radiata - Mellow, K.; Chettri, P.; Kabir, S.; McDougal, R.L.; Cox, M.P.; Stewart, A.; Lange, C.; Steyaert, J.M.; Bradshaw, R.E. (New Zealand Plant Protection, 2016)
Trichoderma cf atroviride is an endophytic soil fungus which has been the target of much research due to its plant growth promoting effects and use as a biocontrol agent. For specific bioactive strains of this species to be used with longlived forest trees such as Pinus radiata they must persist over the long term in the host root system. To investigate the persistence of specific T cf atroviride strains in the roots of P radiata unique regions were identified in the genomes of strains that were more than 997 identical by using next generation sequencing. Based on these unique regions probebased strainspecific quantitative PCR assays were developed. The assays can be used to test strain persistence in nursery and forestgrown seedlings inoculated with mixtures of T cf atroviride strains as well as in laboratory experiments to determine the effect of these strains on plant metabolism and defence.